Answers

2016-04-20T20:28:24+05:30
The above equation is in standard form. now consider p1(X)= kX2 + 3X2 - 8 and P2(x) = 3x3 - 0x2 -5x+k ( now it is  in standard form).                                          consider G(x) = x + 2 = 0 then it becomes x = - 2.                                                    substitute the value of x in both the equation and get the k value.

0
2016-04-20T23:51:14+05:30
X+2=0
X= -2
P(X)= 0
P(-2)= -8K+12-8=0
        -8K= -4
           K=0.5
P(-2)= -24+0+10+K
       -14+K=0
          K=14
HOPE I HELPED YOU!!!
0
thnks for helping..but ur answer is wrong
Is it right